2003
DOI: 10.1002/joc.903
|View full text |Cite
|
Sign up to set email alerts
|

Spring northward retreat of Eurasian snow cover relevant to seasonal and interannual variations of atmospheric circulation

Abstract: An observational study is made of the seasonal and interannual variations of spring snow-disappearance over the Eurasian continent and the circulation mechanisms causing those variations. The spring northward retreat of the snow boundary over the East European Plain (EEP) between 30 and 60°E is faster (0.4°per day) than to the east of the Ural Mountain range (0.3°per day). These migrations of the snow boundary lag behind the appearance of the surface air temperature 0°C by about 1 to 5 pentads.The analyses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 24 publications
5
28
2
Order By: Relevance
“…Advection from southwest shows often features of foehn as well; it is observed in southern Poland in about 12 % days in December and January (Niedźwiedź 2003). A similar influence is observed over east European Plain, where the warm air associated with southwesterly winds and the adiabatic heating of descending air are primarily responsible for the rapid snowmelt in March and April (Ueda et al 2003). The foehn effect influence on the snow cover stability in Poland appears to be much stronger and visible on far larger surface than this one on snow cover duration and snow cover depth analyzed before (Falarz 2007a).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Advection from southwest shows often features of foehn as well; it is observed in southern Poland in about 12 % days in December and January (Niedźwiedź 2003). A similar influence is observed over east European Plain, where the warm air associated with southwesterly winds and the adiabatic heating of descending air are primarily responsible for the rapid snowmelt in March and April (Ueda et al 2003). The foehn effect influence on the snow cover stability in Poland appears to be much stronger and visible on far larger surface than this one on snow cover duration and snow cover depth analyzed before (Falarz 2007a).…”
Section: Discussionsupporting
confidence: 60%
“…However, the impact of circulation changes on the stability of the snow cover in the course of the winter season is less known. Some works studied the influence of atmospheric circulation on midwinter (Grundstein and Leathers 1998) or spring melting snow cover (Ueda et al 2003). Some papers present models of snow cover-atmospheric boundary layer interactions (Strack et al 2003;Rodell and Houser 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In the years of excessive ESSC anomalies, cooling and a cyclonic circulation anomaly in the lower troposphere appeared over the northern part of Eurasia, which weakened east Asia summer monsoon and caused deficient rainfall. By observational studies, Ueda et al (2003) confirmed the earlier findings that the surface temperature decreased in May (usually the seasonal snow-disappearance period) and that there is a weak dynamical linkage between the east European plain snow cover from 30 to 60°E and Asian summer monsoon.…”
Section: Introductionsupporting
confidence: 85%
“…Q is referred to as the apparent heat source because of possible contributions resulting from unresolved eddies associated with dry thermal convection (Yanai et al 1973;Ueda et al 2003). The lower atmospheric heat budget is calculated for the domain shown in Fig.…”
Section: Snowmelt and Atmospheric Heating Processes Over Eastern Mongmentioning
confidence: 99%
“…It is well known that there is a negative correlation between the winter snow cover over the continent and the subsequent Asian summer monsoon, as pointed out for the first time by Blanford (1884). Since then, considerable evidence of such correlation has been accumulated from analyses of satellite-observed snow data (e.g., Hahn and Shukla 1976) and ground-based snow data (e.g., Shinoda 2001;Shinoda et al 2001;Ueda et al 2003) and numerical simulations (e.g., Barnett et al 1989). On the other hand, there have been a few attempts to explore the physical processes that cause snowmelt on the continent (Ueda et al 2003;Iijima et al 2007).…”
Section: Introductionmentioning
confidence: 99%